Impact of TEC Gradients and Higher-Order Ionospheric Disturbances on Spaceborne Single-Pass SAR Interferometry - Krieger, Gerhard; De Zan, F.; Dekker, P. Lopez; Kim, J. S.; Cassola, M. Rodriguez; Moreira, A. (International Geoscience and Remote Sensing Symposium (IGARSS) 2015, 2015)
This paper analyzes the impact of a spatially inhomogeneous ionosphere on spaceborne single-pass SAR interferometry. For this, linear TEC gradients and higher-order irregularities are considered. It is shown that TEC gradients as low as 0.01 TECU/km may already noticeably affect the accuracy of an L-band cross-track interferometer, causing, e.g., horizontal and vertical offsets in the order of 1-2 m. Higher-order perturbations of the electron plasma lead to additional errors that vary nonlinearly with the length of the interferometric baseline. To predict these errors, we model the ionospheric irregularities as the product of a vertical profile and a second-order stationary stochastic process with a 3-D power-law spectrum. The interferometric errors are then derived via a set of projection integrals that express the expected phase error variance as a function of the baseline length and the angular extent of the synthetic aperture. With this model, we show that the phase errors of an L-band single-pass SAR interferometer may reach several tens of degrees under medium turbulence conditions. Since these phase errors are highly correlated among neighboring resolution cells, they cannot be reduced by multi-looking, thereby posing a possible challenge for multiple baseline interferometry and SAR tomography.
DLR Import::2019-04-03
Keywords: ionosphere; irregularity spectrum; SAR interferometry; scintillation; TEC gradients; turbulence